Pathogenesis and management of peripartum coagulopathic calamities (disseminated intravascular coagulation and amniotic fluid embolism) - Levi, Marcel (Thrombosis research, 2013)
Acute coagulopathic peripartum calamities are relatively rare but contribute importantly to maternal morbidity and mortality in the Western world. Abruptio placenta, amniotic fluid embolism, and retained fetal or placental material may lead to fulminant intravascular activation of coagulation which results in thromboembolic complications and consumption coagulopathy causing severe hemorrhage. The central underlying pathophysiological pathway in the coagulopathy associated with these syndromes is the occurrence of tissue factor, released from the placenta and amniotic fluid, in the circulation, in combination with low levels of physiological anticoagulant factors during pregnancy. The diagnosis of DIC may be made trough conventional composite scoring systems employing routine coagulation tests, whereas for the diagnosis of amniotic fluid embolism measurement of insulin like growth factor binding protein-1 seems promising. Therapy is aimed at removing the precipitating factor combined with supportive adjunctive treatment options.